Diagnosis of Bacterial Vaginosis by Acridine Orange Staining and its Comparison to Conventional Methods and Association of Gardnerella vaginalis with Bacterial Vaginosis. - Begum, Naznin; Muazzam, Naima; Shamsuzzaman, SM; Chowdhury, Akhtaruzzaman; Rashid, Aliya; Islam, Dinul (Bangladesh Journal of Medical Microbiology, 2011)
The present study was undertaken to establish the efficacy of acridine orange staining for diagnosis of Bacterial Vaginosis (BV) and association of Gardnerella Vaginalis with BV. Two hundred sexually active females in the age group of 15-45 years, with vaginal discharge and itching, were selected for the study. A detailed history and a thorough clinical examination of all the cases were done. After making the clinical diagnosis of BV by Amsels criteria, diagnosis also carried out with Acridine orange staining, Gram stain, Nugent criteria and isolation of Gard. vaginalis from vaginal fluid. Out of 200 women, 48 (24%) cases were diagnosed as having bacterial vaginosis by applying Amsel’s clinical criteria. The rate of detection of bacterial vaginosis was 23% by Gram stain Nugent criteria and 24.5% by acridine orange staining. Out of the total 48 BV cases, the rate of detection of BV was 100% by Acridine orange staining and 93.87% by Gram-stain Nugent criteria. By Acridine orange staining Lactobacillus and pus cell were also detected which provided an important information about vaginal ecosystem. Acridine orange staining was the most sensitive (100%) method considering Amsel’s criteria as gold standard. The sensitivity of Gram stain Nugent criteria was 93.75% in this study. The specificity of Acridine orange staining was 99.55% and the specificity of Gram stain Nugent criteria was 99.10%. The positive predicative values of acridine orange staining and Gram staining Nugent criteria were 97.96% and 95.74% and the negative predictive values of these tests were 100% and 98.65% respectively. The results of Acridine orange staining test correlated well with that of Amsel’s clinical criteria among the study cases and healthy controls. Key words: Bacterial Vaginosis, Sexually Transmitted Diseases, Amsel’s criteria, Acridine orange, Nugent criteria, Gardnerella vaginalis. DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8468 BJMM 2011; 4(1): 37-42